Cultural heritage, ethics and contemporary migrations - Holtorf, Cornelius, 1968-; Pantazatos, Andreas; Scarre, Geoffrey (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Cultural Heritage, Ethics and Contemporary Migrations breaks new ground in our understanding of the challenges faced by heritage practitioners and researchers in the contemporary world of mass migration, where people encounter new cultural heritage and relocate their own. The volume focuses particularly on issues affecting archaeological heritage sites and artefacts, which help determine and maintain social identity, a role problematised when populations are in flux as a result of immigration. This diverse and authoritative collection brings together international specialists to discuss socio-political and ethical implications for the management of archaeological heritage in global society. The authors come from a range of disciplinary backgrounds and include archaeologists, philosophers, cultural historians and custodians of cultural heritage. The result is a rich mix of contrasting yet complementary viewpoints and approaches. Among the topics discussed are the relations between culture and identity; the potentialities of museums and monuments to support or subvert a people's sense of who they are; and how cultural heritage has been used to bring together communities containing people of different origins and traditions, yet without erasing or blurring their distinctive cultural features. This book is a crucial text for archaeologists, curators, policy-makers and other workers in the heritage field, as well as for archaeologists, philosophers, political scientists and other readers interested in the links between immigration and cultural heritage"--
Cultural heritage, minorities and self-respect / Jonathan Seglow -- Ancient places, new arrivals and the ethics of residence / Paul Gilbert -- Foreign and native soils: migrants and the uses of landscape / Robert Seddon -- Changing demographics in Northern Europe: transforming narratives and identifying obstacles: a case study from Oslo, Norway / Christopher Prescott -- Lasting value: engaging with the material traces of America's undocumented migration "problem" / Jason De Léon and Cameron Gokee -- Concord's migrations / Ivan Gaskell -- Affiliative reterritorialization: the Manco Capac statue and the Japanese community in Peru / Helaine Silverman -- Heritage, participant perspective epistemic injustice, immigrants and identity formation / Andreas Pantazatos -- What is cross-cultural heritage: challenges in identifying the heritage of globalized citizens / Laia Colomer and Cornelius Holtorf -- The uses of heroes: justice, Alexander, and the Macedonian naming dispute / Michael Blake -- Archaeological heritage and migration: well-being, place, citizenship and the social / Marga Diaz-Andreu -- "Everyone's different but we are all the same": a transcultural project in a multicultural class / Cynthia Dunning -- The "place" of the migrant: heritage in the transnational space of a Sydney park / Denis Byrne -- Sharing history: migration, integration and a post-heritage future / Johan Hegardt.
Includes bibliographical references and index.
ARC
Parama
Keywords: Cultural property; Cultural pluralism; Emigration and immigration -- Social aspects; Architecture